2020
DOI: 10.15503/jecs20151.153.166
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and influence of Vocal and Instrumental Improvisation in Music Therapy on children diagnosed with autism. Pilot Study.

Abstract: Autism is a developmental disorder which is difficult to recognize and diagnose. The present study examines the effectiveness of music therapy intervention based on improvisational techniques with the elements of Creative Music Therapy by Paul Nordoff and Clive Robbins and improvisational techniques by Tony Wigram (such as imitating, frameworking, dialogues, holding) on  developmentl of children with Autism (two boys diagnosed with autism - case 1. and case 2), especially in verbal and nonverbal communication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Thus, they clarify that only the application of tests several times with the same individual, by capturing the variance, can allow the individual to be estimated. Several studies have shown that the "Child-Therapist Relationship in Coactive Musical Experience Scale" and the "Musical Communicativeness Scale" have been used more frequently over the years to assess individuals with different diagnoses (Andre, Gomes & Loureiro, 2018 ;Bergmann et al, 2015;Bunt, 2003;Caltabiano, 2010;Carpente & Aigen, 2019;Cripps et al, 2016;Freire, 2014;Mackinlay & Forrest, 2011;Mahoney, 2010;Nordoff & Robbins, 2007;Robarts , 2000;Sampaio, 2015;Spiro et al, 2017;Szweda, 2015;Wood, 2006). This fact demonstrates that these scales have been well…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they clarify that only the application of tests several times with the same individual, by capturing the variance, can allow the individual to be estimated. Several studies have shown that the "Child-Therapist Relationship in Coactive Musical Experience Scale" and the "Musical Communicativeness Scale" have been used more frequently over the years to assess individuals with different diagnoses (Andre, Gomes & Loureiro, 2018 ;Bergmann et al, 2015;Bunt, 2003;Caltabiano, 2010;Carpente & Aigen, 2019;Cripps et al, 2016;Freire, 2014;Mackinlay & Forrest, 2011;Mahoney, 2010;Nordoff & Robbins, 2007;Robarts , 2000;Sampaio, 2015;Spiro et al, 2017;Szweda, 2015;Wood, 2006). This fact demonstrates that these scales have been well…”
Section: Resultsmentioning
confidence: 99%
“…These scales were developed by Nordoff and Robbins (2007) in research initiated in partnership with the University of Pennsylvania. Currently, these scales have been used in several countries to assess people with different diagnoses such as: autism, childhood schizophrenia, severe emotional disorder, brain injury, mental impairment, Tuberous Sclerosis, visual impairment, severe physical impairment, cerebral palsy, Down syndrome, learning disability with aphasia complications, anorexia nervosa and healthy people (Andre, Gomes & Loureiro, 2018;Bergmann et al, 2015;Bunt, 2003;Caltabiano, 2010;Carpente & Aigen, 2019;Cripps et al, 2016;Mackinlay & Forrest, 2011;Mahoney, 2010;Nordoff & Robbins, 2007;Robarts, 2000;Spiro et al, 2017;Szweda, 2015;Wood, 2006). By considering Brazilian context, these scales have undergone studies of translation into Portuguese, validation and reliability (André, 2017;André, Gomes & Loureiro 2017, 2020c, 2020a, 2020b and have been used…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was required that articles were published in a peer-reviewed journal. Eight articles were chosen, including : Geretsegger, Elefant, Mossler and Gold (2014), Geretsegger, Holck, Carpente, Elefant and Kim, (2015), Bieleninik et al (2017), Knapik-Szweda (2015), Vaiouli, Grimmett, and Ruich, (2015), Ghasemtabar et al (2015), Banks (1982), and Schumacher (2013). Based on the thematic analysis, the current most commonly used clinical improvisation techniques with autistic clients are as follows: imitating, reflecting, synchronising, extending, symbolising, holding, incorporating, and rhythmic grounding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tais autores relatam que esta escala apresentou evidências de validade na avaliação de pessoas com Transtornos do Neurodesenvolvimento no contexto musicoterapêutico brasileiro segundo o Modelo Universalista de Validação, desenvolvido por Herdman Fox-Rushby e Badia (1998), utilizado na pesquisa. André, Gomes e Loureiro (2016), ao realizar um estudo de revisão da Escala de Comunicabilidade Musical perceberam naquele período que as publicações referentes à utilização desta escala estava aumentando no decorrer dos anos, tanto para avaliação de pessoas com diagnóstico de Transtorno do Espectro Autista (TEA), relatado pelos autores Bergmann (2015), Bell et al (2014), Bergmann et al (2015, Caltabiano (2010), Mackinlay e Forrest (2011), Mahoney (2010), Szweda (2015), e Wigram e Gold, (2006), quanto para avaliação de pessoas com Transtornos do Neurodesenvolvimento, conforme relatado pelos autores Aigen (1995) e Mahoney (2010), pessoas saudáveis, conforme apresentado pelos autores Australia (2008), Bunt (2003), Rahman (2008) e Wood (2006) e pessoas com diagnóstico de anorexia nervosa, apresentado no estudo de Robarts (2000).…”
Section: Introductionunclassified